2005
DOI: 10.1002/fld.1007
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of two-dimensional laminar incompressible offset jet flows

Abstract: SUMMARYTwo-dimensional transient laminar incompressible o set jet is simulated numerically to gain insight into convective recirculation and ow processes induced by an o set jet. The behaviour of the jet with respect to o set ratio (OR) and Reynolds number (Re) are described in detail. The transient development of the velocity is simulated for various regions: recirculation, impingement and wall jet development. It is found that the reattachment length is dependent on both Re and OR for the range considered. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 33 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…He confirms that it is difficult to acquire the accurate size and the location of obstacles that do not produce a deflected flow. A Steady-state heat transfer study between a slab and a fluid was carried out experimentally, for a two-dimensional laminar incompressible wall jet over a backward-facing step by Kanna et al,2005. The Nusselt number evolution is determined for several Reynolds number (Re), fluid property (Pr), and solid to fluid conductivity ratio.…”
Section: Fig 1 the Geometry Of The Configurationmentioning
confidence: 99%
“…He confirms that it is difficult to acquire the accurate size and the location of obstacles that do not produce a deflected flow. A Steady-state heat transfer study between a slab and a fluid was carried out experimentally, for a two-dimensional laminar incompressible wall jet over a backward-facing step by Kanna et al,2005. The Nusselt number evolution is determined for several Reynolds number (Re), fluid property (Pr), and solid to fluid conductivity ratio.…”
Section: Fig 1 the Geometry Of The Configurationmentioning
confidence: 99%
“…Based on computational cost and agreement with experimental data, these authors indicated that standard k-ε model is more appropriate than others. Rajesh Kanna and Das (2005) numerically investigated the influence of offset ratio and Reynolds number of a 2D offset jet on the mean flow parameters such as local maximum velocity decay, entrainment, reattachment length, recirculation eddy structure, and vorticity distribution on the lower wall. Vishnuvardhanarao and Das (2008), using the Reynolds-averaged Navier-Stokes equations and standard k-ε turbulent model, studied the mean flow field and thermal characteristics of 2D offset jets with offset ratio of 3, 7, and 11.…”
Section: Introductionmentioning
confidence: 99%